Board structures, ownership structure and firm value in Malaysian public listed manufacturing companies - Lee, Wen Chiat (Universiti Malaysia Sarawak (UNIMAS), 2011)
(ThiS study examines the relationships between board structure variables which are board size, board independence, board monitoring intensity and firm value. The sample covers Malaysian public listed manufacturing companies in year 2008. In addition, the relationship between insider ownership and firm value is also examined. The data coUected from Bursa Malaysia were estimated using Ordinary Least Square (OLS) regression analY~ The results show that all board size, board independence and board monitoring intensity have negative relationships with board value whereas insider ownership has non-linear relationship with the finn value. The study also reveals that Tobin's Q is better than ROA to explain the relationships between board structure variables, insider ownership and firm value, respectively.